PROGRAM PEMBELAJARAN TAHSIN AL-QUR'AN DI MTSN KELAS VIII BARITO SELATAN - Khoir, Miftahul; Aisyah, Siti Nor (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
This study aims to determine how the Tahsin Al-Qur'an Learning Program at MTsN Barito Selatan Class VIII and the supporting and inhibiting factors of the Tahsin Al-Qur'an Learning Program at MTsN Barito Selatan Class VIII. This field research is descriptive in nature which focuses on the phenomena that occur in the field. The subjects of this study were the subject teachers of the Tahsin Al-Qur'an Learning Pro- gram at MTsN Barito Selatan. The object of this study is the Tahsin Al-Qur'an Learning Program at MTsN Barito Selatan. To obtain field data, both the Tahsin Al-Qur'an learning program and the factors that influence it, observation, interview, Oral Test and documentary techniques were used. Based on the results of this study, in general, Tahsin Al-Qur'an Learning includes stages regarding the steps of the learning process, time and place of Tahsin Al-Qur'an learning, with learning effectiveness in the good category. The preparation process with reading prayers before studying, stating learning objectives, preparing study guide books or the Qur'an, the media used such as study guide books and learning videos via cellphone media, the methods used are lectures and Tahsin Al-Qur'an, the learning time of the Tahsin Al-Qur'an program is carried out in the morning three times a week for 2 hours of learning and is divided per day for each class VIII in one week with a duration of 50 minutes per meeting, the place of implementation of learning is in the classroom/prayer room/hall, learning evaluation includes the implementation of evaluations, the time of implementation of evaluations and types of evaluations. Data on supporting and inhibiting factors for the Tahsin Al-Qur'an learning program at MTsN class VIII Barito Selatan. Supporting factors include the intention and motivation to learn and the level of student participation in learning Tahsin Al-Qur'an. Inhibiting factors include the teacher's chasing style, the teacher's understanding of the material, and facilities and infrastructure.